Inflation Outlook — The Costs of War drive prices up to new heights - Johannes Mayr (Wirtschaftsdienst)
Abstract The Russian government’s attack on Ukraine and the spiral of sanctions that has been set in motion have heightened inflationary pressure — especially in Europe. The EU’s high dependency on Russian oil and gas imports harbours the risk that inflation in Europe will rise significantly and that the economy will suffers from a loss of purchasing power. The pressure on policymakers to take counter-measures is growing. However, the options are limited in the short term and economically very costly. And longer-term consequences must be taken into account. Energy policy and climate policy must be closely linked.